Annual Plan West Bengal 1999-2000 Volume I - Planning Commission (Planning Commission, 1999)
Along with this priority for land reforms, it has become essential for sustaining the process of growth and employment generation in agriculture, to formulate afresh and with a view from the State as a whole, a comprehensive plan for cropping pattern for each district, block and Gram Panchayat by involving through the Panchayats the local common farmers. This plan for cropping pattern will be worked out by the first half of the next year, and while working out this plan, a special priority will have to be so accorded as to reduce for all the major crops the gap between the State’s demand and the internal supply within the time frame of the Ninth Five Year Plan (1997-2002).
Development and Planning Department Government of West Bengal
Development and Planning Department Government of West Bengal